Perceptions of social emotional learning needs in high poverty schools - Generali, Margaret M.; Yavuz, Olcay; Parzych, Jennifer (Journal of Contemporary Administrative Science, 2018)
This paper explores the perceived social emotional learning needs of students in high poverty schools. Social emotional learning (SEL)is recognized within the literature as critical to success in school and in life. Emergingwork supports the acquisition of a SEL skillset within grades kindergarten through twelve ( K-12) schools. This survey examines the perceptions of social emotional needs as reported by students, parents and school faculty members across four different high poverty schools in the USA. Findings provide effective strategies and valuable data for school leaders, educators, and counselors in addressing the social emotional needs of urban students.
Keywords: dept.csp; dept.edl; peer-reviewed; ⛔ No DOI found

Counseling strategies for empowering people living in poverty: the I‐CARE model - Foss-Kelly, Louisa L.; Generali, Margaret M.; Kress, Victoria E. (Journal of Multicultural Counseling and Development, 2017)
Poverty has an impact on mental health and the counseling process in profound ways; however, counselors may fail to recognize the importance of poverty in clients' lives. The authors propose a model to help counselors navigate the complexities of counseling clients who are living in poverty. The I-CARE Model may help counselors develop insight about personal biases, acknowledge harsh realities of poverty, remove barriers to growth, and expand on the clients' own strengths.
Keywords: I-CARE Model; counseling; counselor; counselors; dept.csp; dura mater; human; human experiment; mental health; model; poverty; socioeconomic status

Making Choices and Reducing Risk (MCARR): School Counseling Primary Prevention of Substance Use - Foss-Kelly, Louisa L.; Generali, Margaret M.; Crowley, Michael J. (Professional Counselor, 2021)
The consequences of adolescent drug and alcohol use may be serious and far-reaching, forecasting problematic use or addictive behaviors into adulthood. School counselors are particularly well suited to understand the needs of the school community and to seamlessly deliver sustainable substance use prevention. This pilot study with 46 ninth-grade students investigates the impact of the Making Choices and Reducing Risk (MCARR) program, a drug and alcohol use prevention program for the school setting. The MCARR curriculum addresses general knowledge of substances and their related risks, methods for evaluating risk, and skills for avoiding or coping with drug and alcohol use. Using a motivational interviewing framework, MCARR empowers students to choose freely how they wish to behave in relation to drugs and alcohol and to contribute to the health of others in the school community. The authors hypothesized that the implementation of the MCARR curriculum would influence student attitudes, knowledge, and use of substances. Results suggest that the MCARR had a beneficial impact on student attitudes and knowledge. Further, no appreciable increases in substance use during the program were observed. Initial results point to the promise of program feasibility and further research with larger samples including assessment of longitudinal impact.
Keywords: Adolescents; Counselor Role; Decision Making; Grade 9; Health Behavior; High School Students; Knowledge Level; Prevention; Program Effectiveness; Risk; School Counseling; School Counselors; Student Attitudes; Substance Abuse; Urban Schools; dept.csp; peer-reviewed